Mixed‐Linker Hybrid Superpolyhedra for the Production of a Series of Large‐Pore Iron(III) Carboxylate Metal–Organic Frameworks. Issue 19 (3rd April 2013) - Chevreau, Hubert; Devic, Thomas; Salles, Fabrice; Maurin, Guillaume; Stock, Norbert; Serre, Christian
Abstract : It's all in the mix ! Metal–organic frameworks (MOFs) were constructed from iron(III) trimers and mixtures of di‐ and tricarboxylate linkers. The dicarboxylate linker determined the size and shape of the pores in one series of materials with an interwoven structure and also enabled the introduction of different functionalities. Another mesoporous iron(III) MOF based on hybrid supertetrahedra had an extended β‐cristobalite structure (see picture).